Determining Intention to Use Smartphone Banking Application among Millennial Cohort in Malaysia - Karim, Md Wasiul; Ulfy, Mohammad Arije; Huda, Md. Nazmul (International Journal of Management and Sustainability, 2020)
The numbers of smartphone banking applications have risen over the years. Gaining popularity of smartphone banking apps resulted in many millennials switching from internet banking to mobile banking apps. The purpose of this study is to determine the factors that influence millennials’ behavioral intention to use smartphone banking applications. The research framework is developed base on the technology acceptance model (TAM). A total of 310 questionnaires were distributed to the users of smartphone banking apps in Klang Valley area of Malaysia. The partial least squares structural equation modeling (PLS-SEM) technique is employed to process and analyze the data. The two-step approach involves in analyzing the data. Firstly, measurement model assessment which is associated with indicator loadings. Secondly, the structural model which is associated with path coefficient measures. The findings from this study reveal that perceived usefulness, perceived ease of use, perceived trust and perceived security have a positive and significant influence on behavioral intention where perceived security has a stronger influence on trust and perceived ease of use on perceived usefulness. The findings from this study will benefit the banking apps service provider to ensure the best mechanism to be implemented to gain customers' attention.